Associations between maternal dietary scores during early pregnancy with placental outcomes - Teo, Shevaun M.; Murrin, Celine M.; Mehegan, John; Douglas, Alexander; Hébert, James R.; Segurado, Ricardo; Kelleher, Cecily C.; Phillips, Catherine M. (Frontiers in Nutrition, 2023)
Background and Aims Individual macronutrient and micronutrient effects on placental growth have been widely investigated. However, the influence of overall maternal diet is relatively unknown. Therefore, the aim of this study is to examine associations between a range of maternal dietary scores during early pregnancy with placental outcomes, and to investigate whether there is evidence of sexual dimorphism. Methods This analysis of the Lifeways Cross-Generational Cohort includes 276 mother-child pairs. A validated 148-item semi-quantitative food frequency questionnaire assessed maternal diet in early pregnancy. Dietary scores reflecting dietary quality (Healthy Eating Index (HEI-2015), Dietary Approaches to Stop Hypertension (DASH)), dietary inflammatory potential (Dietary Inflammatory Index (DII) and the energy adjusted DII (E-DII)), dietary antioxidant status (Dietary Antioxidant Quality (DAQ)), and glycemic and insulinemic loads/indices (GL/GI, IL/II) were calculated. Linear regression analyses assessed maternal dietary score relationships with untrimmed placental weight (PW) and birth weight:placental weight (BW:PW) ratio. Results In fully adjusted models, maternal E-DII and GI were positively associated, and HEI-2015 and DAQ were negatively associated with PW (B: 12.31, 95% CI: 0.41, 24.20 p=0.04, B: 4.13, 95% CI: 0.10, 8.17, p=0.04, B: -2.70, 95% CI: -5.03, -0.35 p=0.02 and B: -15.03, 95% CI: -28.08, -1.98 p=0.02, for E-DII, GI, HEI-2015 and DAQ respectively). Maternal DAQ associations with BW:PW ratio were attenuated. When stratified by sex, maternal GI and pregnancy-specific DAQ were associated with PW in female offspring (B: 5.61, 95% CI: 0.27, 10.96, p=0.04 and B: -15.31, CI: -30.35, -0.27, p=0.046). Maternal E-DII and HEI-2015 were associated with PW in males (B: 24.31, 95% CI: 5.66, 42.96, p=0.01 and B: -3.85, 95% CI: -7.47, -0.35, p=0.03 respectively). Conclusion The results of this novel investigation suggest that maternal diet may influence placental development. Female fetuses may be more sensitive to increased glucose levels whereas male fetuses may be more susceptible to in-utero stresses that are regulated by inflammatory pathways and overall diet quality. Hence, early pregnancy offers an opportune time for a mother to prioritise dietary changes that focus on reducing inflammatory and glycemic responses.